2014
DOI: 10.1021/am501247u
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Al-Doping Profile and Accompanying Electrical Properties of Rutile-Phased TiO2 Thin Films

Abstract: The role of Al dopant in rutile-phased TiO2 films in the evaluation of the mechanism of leakage current reduction in Al-doped TiO2 (ATO) was studied in detail. The leakage current of the ATO film was strongly affected by the Al concentration at the interface between the ATO film and the RuO2 electrode. The conduction band offset of the interface increased with the increase in the Al dopant concentration in the rutile TiO2, which reduced the leakage current in the voltage region pertinent to the next-generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The same concentration profile of Al ion in ATO films also obtained from the time-of-flight secondary ion mass spectroscopy profile and X-ray photoemission spectroscopy analysis. These results were confirmed that Al concentration both at the interface and depth-direction can be controlled by Al 2 O 3 deposition location [5]. The capacitance density of ATO films were about 95 fF/μm 2 regard- www.pss-rapid.com status solidi physica rrl less location of Al doping.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…The same concentration profile of Al ion in ATO films also obtained from the time-of-flight secondary ion mass spectroscopy profile and X-ray photoemission spectroscopy analysis. These results were confirmed that Al concentration both at the interface and depth-direction can be controlled by Al 2 O 3 deposition location [5]. The capacitance density of ATO films were about 95 fF/μm 2 regard- www.pss-rapid.com status solidi physica rrl less location of Al doping.…”
supporting
confidence: 68%
“…In Ref. [5], the Schottky barrier height was taken to be 1.49-1.59 eV. However, taking the reference Schottky barrier height as 1.2 eV and assigning 0.1 eV difference between the two interfaces resulted in the much better fitting with not only the J-V curve shape but also the absolute J values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dielectric constant for this ATO thin film was ;60, which was significantly smaller than the expected ;100 for a rutile phase because of the decrease in crystallinity from the Al dopant. The tremendous leakage current reduction in this report was likely because Al doping increased the CBO to its ideal value via the acceptorlike characteristics of the Al ions in the TiO 2 [52,53]. These results [53,55] showed that the electrical properties of ATO depended on the Al doping profile.…”
Section: Al-doped Tiomentioning
confidence: 56%